2017
DOI: 10.1007/s10584-017-2091-0
|View full text |Cite
|
Sign up to set email alerts
|

Climate variability of heat wave and projection of warming scenario in Taiwan

Abstract: This study examined the climate variability of heat wave (HW) according to air temperature and relative humidity to determine trends of variation and stress threshold in three major cities of Taiwan, Taipei (TP), Taichung (TC), and Kaohsiung (KH), in the past four decades . According to the data availability, the wet-bulb globe temperature (WBGT) heat stress for the three studied cities was also calculated for the past (2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012) and simulated under the future … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…The warming trend has been distinct in the urbanised basin areas. Both the intensity and frequency of hot summer days have increased significantly in the last four decades ( Bai, Juang, & Kondoh, 2011 ; CWB, 2014 ; Lin, Chien, Su, Kueh, & Lung, 2017 ). This warming tendency places pressure on electricity networks due to rising cooling demands and may increase heat-related health problems, especially given Taiwan’s increasingly elderly population ( Chen, Wu, Pan, Chen, & Lung, 2016 ).…”
Section: Data and Analytical Methodsmentioning
confidence: 99%
“…The warming trend has been distinct in the urbanised basin areas. Both the intensity and frequency of hot summer days have increased significantly in the last four decades ( Bai, Juang, & Kondoh, 2011 ; CWB, 2014 ; Lin, Chien, Su, Kueh, & Lung, 2017 ). This warming tendency places pressure on electricity networks due to rising cooling demands and may increase heat-related health problems, especially given Taiwan’s increasingly elderly population ( Chen, Wu, Pan, Chen, & Lung, 2016 ).…”
Section: Data and Analytical Methodsmentioning
confidence: 99%
“…This is also the reason ground temperatures are typically higher than air temperatures. Although air temperatures are commonly used for heatwave risk assessment (e.g., [41,42]), our results suggest that ground temperature is a better indicator of UHI effects. Although the results are only for one of the 61 target days, examination of the data for the other days showed that ground temperatures in urban areas were high on most of the target days.…”
Section: ) Ground Temperatures (C2)mentioning
confidence: 66%
“…HTEs have been widely discussed in climate change‐related studies. In Taiwan, the number (Li, ; Lin et al, ) of hot days has increased considerably over the past few decades. Understanding the multiscale variability that favors HTE occurrence and identifying possible precursors for HTE prediction and early warning are therefore essential.…”
Section: Introductionmentioning
confidence: 99%
“…The interannual variations in summer HTEs in China have been attributed to variation in the WNP SH, which in turn have been ascribed to ENSO's lagged influence and associated warming of the Indian Ocean basin (Hu et al, ; Hu et al, ; Wang et al, ). Regarding the interannual variability of HTEs in Taiwan, numerous studies have examined and explained the trends (Hsu et al, ; Lai & Cheng, ; Lu et al, ) and the decadal variability (Lin et al, ), but fewer studies have examined the impact of ENSO.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation